Penerapan Metode Problem Solving Pada Pembelajaran Pendidikan Agama Islam dan Budi Pekerti Siswa Kelas V di Sekolah Dasar IT Abdurrahman Bin ‘Auf: Implementation of the Problem Solving Method in Islamic Religious Education and Character Education Learning for Fifth Grade Students at IT Elementary School Abdurrahman Bin ‘Auf - Novayani, Irma (Literasi: Jurnal Pendidikan Guru Indonesia, 2025)
The purpose of this study is to examine the application of the problem-solving method in teaching Islamic religious education and character education in V class students at Abdurrahman Bin 'Auf Elementary School, as well as the supporting and inhibiting factors in teaching Islamic religious education and character education. The research method used a descriptive qualitative approach, collecting data through observation, interviews, and documentation. The subjects were the principal, Islamic religious education teachers, and on V class students. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results in the application of the problem-solving method involved several stages: identifying problems, gathering information, presenting material, conducting questions and answers, and drawing conclusions. This method was able to increase student engagement and understanding in learning, as evidenced by students' faster responses to the material and their involvement in discussions. Supporting factors in the implementation of this method included school support and teachers' freedom to choose learning methods. Inhibiting factors included teacher factors, student factors, and a less conducive classroom environment.